النظام القانوني لعقد البوت ".B. O. T" وتطبيقاته في النظام القانوني الجزائري - رحال، جمال (جامعة الجلفة, 2023)
تعد عقود البوت "B.O.T" من أهم عقود التنمية الاقتصادية، وغالبا ما تثير عقود البوت الـ "B.O.T" المشكلات القانونية نظرا لاستناد كل طرف من طرفي العلاقة التعاقدية لنظام قانوني مختلف عن الآخر، فالدولة الطرف الرئيسي في العقد شخص من أشخاص القانون العام، والمستثمر شخص من أشخاص القانون الخاص، مما يؤدي إلى اختلاف المراكز القانونية لأطراف العقد. لذا سنحاول من خلال هذه البحث توضيح مفهوم عقود البوت "B.O.T"، كما نحاول في هذا البحث الوقوف على ملامح عقود البوت "B.O.T" في النظام القانوني الجزائري، لأن المشرع الجزائري لم يضع تشريعا عاما ينظم فيه الجوانب القانونية المختلفة لهذا العقد. The "B.O.T" contracts are considered as one of the most important contracts of economic development, which are often the cause of many legal problems due to the fact that both parties of the contractual relationship are based on a legal system which is different from the other. The country which is the main party of the contract is considered as a person under public law and the investor is an individual under private law, which leads to the diversity of the legal position of the parties to the contract. Which is why I have tried in this research to clarify the concept of "B.O.T" contracts, as in this research we try to hold on the characteristics of "B.O.T" contracts in the Algerian legal system, because the legislator Algerian has not put legislation governing the various legal aspects of these contracts.An abstract is a brief, comprehensive summary of the contents of the article In 150 words a rate of four to five lines
Keywords: عقود البوت -- نقل الملكية -- العقود الإدارية -- التنمية الاقتصادية -- التشريعات الجزائرية